Optical electromagnetic radiation density spherical geometric electric and magnetic phase by spherical antiferromagnetic model with fractional system - Khalil, E. M.; Korpinar, T.; Korpinar, Z.; İnç, Mustafa (Soc Mexicana Fisica, 2021)
In this article, we firstly consider a new theory of spherical electromagnetic radiation density with an antiferromagnetic spin of timelike spherical t-magnetic flows by the spherical Sitter frame in de Sitter space. Thus, we construct the new relationship between the new type electric and magnetic phases and spherical timelike magnetic flows de Sitter space S-1(2) Also, we give the applied geometric characterization for spherical electromagnetic radiation density. This concept also boosts to discover of some physical and geometrical characterizations belonging to the particle. Moreover, the solution of the fractional-order systems is considered for the submitted mathematical designs. Graphical demonstrations for fractional solutions are presented to an expression of the approach. The collected results illustrate that mechanism is a relevant and decisive approach to recover numerical solutions of our new fractional equations. Components of performed equations are demonstrated by using approximately explicit values of physical assertions on received solutions. Finally, we construct that electromagnetic fluid propagation along fractional optical fiber indicates a fascinating family of fractional evolution equations with diverse physical and applied geometric modeling in de Sitter space S-1(2).
Keywords: magnetic particle; optical fiber; geometric phase; evolution equations; traveling wave hypothesis; antiferromagnetic model